«Puntos de fuga» en Carara: Convivencia y construcción social del porvenir - Lobo Montoya, Diego (2013)
This article seeks to comprehend the processes of eco-self-organization of society in its true potential. Thus, this article discusses some examples in the reality of Carara and its organic connections with a broader bioethical and systemic approach. Some of the qualities found in the rural societies of Carara are true autopoietic forces that have the power to establish “vanishing points” to reconstruct local society in a planetary perspective.